Enhancing industrial maintenance planning: Optimization of human error reduction and spare parts management - Vahideh Bafandegan Emroozi; Mostafa Kazemi; Mahdi Doostparast (Operations Research Perspectives)
Maintenance is pivotal in the industrial sector, influencing efficiency, reliability, safety, and profitability. An organized spare parts inventory supports maintenance efforts by minimizing downtime, ensuring safety, and optimizing maintenance budgets. Effective spare parts management enhances maintenance operations and improves cash flow. Conversely, human error can greatly diminish the effectiveness of maintenance efforts. This paper presents a mathematical model aimed at minimizing costs through optimized preventive maintenance (PM) planning, effective spare parts inventory control, and reduction of human error. The study provides decision-makers with crucial insights for strategically managing maintenance procedures while accounting for the effect of human error. The model is validated in real-world scenarios through sensitivity analysis, focusing on the shape parameter of the Weibull distribution, and the equipment's effective rate. Findings reveal that as the number of periods increases, maintenance operations follow a specific, predictable cycle. Moreover, the optimal human error probability (HEP) for cost minimization is identified as 0.02. These insights guide decision-makers in recognizing factors influencing human error and implementing proactive strategies to enhance maintenance performance.